Case Report: Prenatal diagnosis of fetal tetrasomy 9p initially identified by non-invasive prenatal testing - Yu, Jialing; Chen, Na; Chen, Min; Shen, Min; Qian, Yeqing; Dong, Minyue (Frontiers in Genetics, 2022)
Tetrasomy 9p is a rare syndrome characterized by fetal growth restriction, Dandy- Walker malformation, cardiac anomaly and facial abnormality which is provoked by ultrasound. Herein we report a fetus of tetrasomy 9p without obvious phenotype during the first trimester identified by Non-invasive prenatal testing (NIPT). NIPT revealed that the gain of 9p24.3-9p11 with approximately 46.36Mb in size. Karyotyping of amniocytes indicated an additional marker in all metaphase. Chromosome microarray (CMA) and Fluorescence in situ hybridization (FISH) on uncultured amniocytes revealed tetrasomic of 9p24.3q13 and the supernumerary chromosome consist of two copies of 9p arm which was inverted. All of these approaches suggested that the karyotype of the amniocytes was 47,XY,+idic(9)(q13), indicating that multiple techniques were crucial to the prenatal diagnosis.